Active vacuum brazing of CNT films to metal substrates for superior electron field emission performance. Issue 1 (6th February 2015) - Longtin, Rémi; Ramon Sanchez-Valencia, Juan; Shorubalko, Ivan; Furrer, Roman; Hack, Erwin; Elsener, Hansrudolf; Gröning, Oliver; Greenwood, Paul; Rupesinghe, Nalin; Teo, Kenneth; Leinenbach, Christian; Gröning, Pierangelo
Abstract: The joining of macroscopic films of vertically aligned multiwalled carbon nanotubes (CNTs) to titanium substrates is demonstrated by active vacuum brazing at 820 °C with a Ag–Cu–Ti alloy and at 880 °C with a Cu–Sn–Ti–Zr alloy. The brazing methodology was elaborated in order to enable the production of highly electrically and thermally conductive CNT/metal substrate contacts. The interfacial electrical resistances of the joints were measured to be as low as 0.35 Ω . The improved interfacial transport properties in the brazed films lead to superior electron field-emission properties when compared to the as-grown films. An emission current of 150 μ A was drawn from the brazed nanotubes at an applied electric field of 0.6 V μ m −1 . The improvement in electron field-emission is mainly attributed to the reduction of the contact resistance between the nanotubes and the substrate. The joints have high re-melting temperatures up to the solidus temperatures of the alloys; far greater than what is achievable with standard solders, thus expanding the application potential of CNT films to high-current and high-power applications where substantial frictional or resistive heating is expected.